Exploring the Interplay of Mathematical Perception, Learning Independence, and Parental Attention in Mathematics Learning Achievement - T. Tintia; I Nyoman Arcana; Dafid Slamet Setiana; Krida Singgih Kuncoro (SIGMA DIDAKTIKA: Jurnal Pendidikan Matematika, 2023)
This study aims to investigate the existence of a positive and significant relationship between mathematical perception, learning independence, and parental attention with mathematics learning achievement among eighth-grade students at SMP N 1 Parittiga. Additionally, the study aims to identify the variables that contribute the most to students' mathematics learning achievement at SMP N 1 Parittiga. The research method used in this study is ex post facto, involving a sample of 25 students. Data were collected through the completion of questionnaires on mathematical perception, learning independence, and parental attention, as well as by collecting documentation of students' midterm mathematics grades in eighth grade at SMP N 1 Parittiga. Data analysis included multiple correlation tests and partial correlation tests. The results of the study indicate that there is no significant relationship between mathematical perception, learning independence, and parental attention with mathematics learning achievement. Furthermore, no independent variable was found to have a dominant contribution to the dependent variable. However, it is important to consider other factors that may influence students' mathematics learning achievement in future research, such as intrinsic motivation and environmental factors in the home learning environment. Additionally, conducting research with a larger sample size and using more valid and reliable measurement tools is recommended to obtain more accurate and generalizable results.